The validity of learning tools based on guided inquiry learning on the topic of respiratory system - Halid, Rizka; Lamondo, Djuna; Yusuf, Frida Maryati; Husain, Ilyas; Latjompoh, Masra; Solang, Margaretha (Univeritas Papua, 2023)
This research aims to analyze the validity of learning tools based on guided inquiry learning on respiratory system material. Research and development of the ADDIE model were used in this research. This research was limited to the